Methods for building, rebuilding, and preserving historical structures - Dorozhko, Yevhen; Lohvynenko, Vladyslav; Berezovetska, Iryna; Кyslytsia, Lina; Kapshuk, Olha (Edelweiss Applied Science and Technology, 2025)
The article is devoted to analyzing construction, reconstruction, and restoration technologies for historical objects in the context of architecture and building. It examines various techniques and methodologies, encompassing historical and contemporary approaches. The article discusses concepts and types and the importance of preserving cultural heritage and using cutting-edge technologies to restore historical sites. This study aims to examine and analyze the construction, reconstruction, and restoration technologies employed for historical objects in architecture and buildings. The research methodology analyzes literary sources, historical documents, and scientific articles covering historical objects' construction, reconstruction, and restoration. It also utilizes data from practical experience in restoration and construction projects. The methodology includes the analysis and comparison of different approaches, the study of historical contexts, and the evaluation of the impact of technologies on the preservation of cultural heritage. Throughout the research, various technologies for the construction, reconstruction, and restoration of historical objects were examined. It was found that these processes are complex and multifaceted, requiring a careful approach and the use of diverse methods and tools. The research demonstrated that modern technologies effectively restore and preserve historical objects, ensuring their long-term operation and protection from wear. However, addressing budget constraints, data loss, and other challenges requires a comprehensive approach and collaboration among various stakeholders. In light of the considerations above, further research in the construction and restoration field can contribute to the further development and improvement of these processes to preserve and restore cultural heritage for future generations.